Positions and characteristics of tracer particles in the Ain River channel (2015) - Arnaud, Fanny; Paquier, André; Vázquez-Tarrío, Daniel; Camenen, Benoit; Le Coz, Jérôme; Michel, Kristell; Naudet, Grégoire; Pella, Hervé; Piégay, Hervé (In: Arnaud, F et al. (2023): Field, probabilistic and 2D numerical modeling dataset on gravel mobility in the Ain River (2013-2017) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.954231, 2023)
This dataset describes 473 PIT-tagged particles recovered during the field survey in July 2015 in the Ain River channel, including the positions of inferred tracers, i.e. tracers missing in 2015 that were found in 2017 and remained immobile throughout.
Keywords: 2D modeling; Ain River; Gravel mobility; PIT tags; Probabilistic modeling